2008
DOI: 10.4000/archeosciences.1032
|View full text |Cite
|
Sign up to set email alerts
|

Archaeometric data on production and circulation of Neolithic Serra d’Alto ware in southern Italy during the fifth millennium BC

Abstract: Mid/Late Neolithic Serra d’Alto ware was widely diffused in southern Italy during the fifth millennium BC and shows homogeneous formal and technical features. Its wide distribution and frequent occurrence in funerary or cultual contexts have led many scholars to emphasise its exchange value. The issue of the circulation of finished pots rather than of a production model in different areas of Southern Italy, is explored by means of petrologic, mineralogical and chemical analyses of pottery samples from Apulia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Traditional archaeometric concerns would focus only on verifying or refuting the local or exotic origin of these vessels. Indeed, work in north Calabria (Muntoni and Laviano, 2008;Muntoni et al, 2009) has shown that, at least at the site of Favella, they were locally produced (although see Spataro, 2009 for an argument of regional production and distribution in southeastern Italy). Our work, however, shows that local Neolithic potters of the Umbro plateau had access to two different sources of clays that could be used in the production of such vessels: the Pliocene Marls and some of the Varicoloured Clays.…”
Section: Summary and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Traditional archaeometric concerns would focus only on verifying or refuting the local or exotic origin of these vessels. Indeed, work in north Calabria (Muntoni and Laviano, 2008;Muntoni et al, 2009) has shown that, at least at the site of Favella, they were locally produced (although see Spataro, 2009 for an argument of regional production and distribution in southeastern Italy). Our work, however, shows that local Neolithic potters of the Umbro plateau had access to two different sources of clays that could be used in the production of such vessels: the Pliocene Marls and some of the Varicoloured Clays.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…We can then correlate continuities and disruptions in technology and landscape use with other archaeological data suggesting social reorganization of southern Italy (e.g., new burial customs and/or new spatial distributions of new pottery types) to examine how long-term technological traditions respond to broader social change and affect the interactions between humans, landscapes and materials. Similarly, once we understand potters' choices in each time period at the Umbro plateau, we can compare them to published data from other sites in Calabria and southern Italy (e.g., Morter and Iceland, 1995;Muntoni and Laviano, 2008;Spataro, 2009;Williams, 1980) to understand the degree to which technological knowledge was shared over wide regions and what this suggests about regional and inter-regional social interactions.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Cabe destacar la cerámica de Serra d'Alto, originaria del sur de Italia. Esta presenta una amplia distribución por el centro y norte de Italia, apareciendo frecuentemente en contextos funerarios, hecho que ha llevado a diferentes autores a considerarla como un objeto con valor de intercambio (Muntoni, 2012). Estudios recientes han evidenciado que las cerámicas de este estilo encontradas en el centro y norte de Italia no serían productos exportados desde el sureste, sino imitaciones locales (Bernabò et al, 2010;Mazzieri et al, 2012;Aranguren et al, 2014).…”
Section: Tradiciones Cerámicas Sistemas De Intercambio Y Redes Social...unclassified
“…Collections of lithic materials constitute a valuable heritage, since they assemble and exhibit raw materials used in Prehistory and represent a powerful tool of knowledge of human civilizations, in particular when a significant contribution is given by the scientific studies on their samples (Muntoni 2012).…”
Section: Introductionmentioning
confidence: 99%